Surrounding rock failure analysis of retreating roadways and the control technique for extra-thick coal seams under fully-mechanized top caving and intensive mining conditions: A case study. (March 2020) - Yan, Hong; Zhang, Jixiong; Feng, Ruimin; Wang, Wei; Lan, Yiwen; Xu, Zhijun
Highlights: Failure modes of the supporting structure in intensive mining roadways were concluded. A physical model for dynamic failure characteristics of coal roadways was built. The single mechanical yieldable props with high constant resistance were tested in the field. Abstract: Most retreating roadways in extra-thick coal seams, are affected by multiple mining activities under fully-mechanized top caving mining conditions. Surrounding rock deformation and stress evolution of the roadways are complex under intensive mining activities due to interlayers occurrence in top thick coal roof developed in fissures and fractures in coal seams, and large cross-section of the roadways. If no appropriate support techniques and optimization measures are taken under such mining conditions, consequences such as severe bedding separation, large deformation of surrounding rock, and large-area top caving disaster, can occur. Therefore, the investigation of surrounding rock deformation and failure mechanism of retreating roadways and the control technique for extra-thick coal seams under fully-mechanized top caving and intensive mining conditions, is the key for stability control for this type of roadway. Various research methods were adopted comprehensively in this study including field investigation, monitoring and statistics, experimental tests, physical similarity simulation, and field testing. Taking the return airway # 5110 in the main mining coal seam # 3–5 with the thickness of 14.7 m of Tashan coal mine, Datong Coal Mine Group as the case, failure characteristics of roof supporting structures of the return airway # 5110 undergoing retreating mining of the upper coal panel # 8109 and the current mining panel # 8110 were investigated. By employing bedding separation acquisition monitoring device and force-meters, surrounding rock deformation, carrying the load of rock bolts and cables, and bedding separation, were monitored and analyzed. The monitoring was done by the surrounding deformed rock where loading characteristics of the supporting structures in the roadway # 5110 were obtained under intensive mining conditions for the extra-thick coal seam. Stress evolution during the process from roadway stability to instability was characterized experimentally under different lateral pressure conditions by using physical similarity simulation. On this basis, the single mechanical yieldable prop with high constant resistance was proposed to support the surrounding rock of retreating roadways in extra-thick coal seams. The analysis was carried on the structure and on the working mechanisms of the prop set where its working resistance under the height of 3 m, support patterns, and support techniques, and then field tests were conducted in the retreating roadway # 5110. The typical monitoring results showed that the contraction area of the trial roadway ahead of the working face decreases significantly, and that the largest displacement between two coal sides is no more than 428 mm (the largest roof subsidence is no more than 663 mm). The test results show that good control effect on surrounding rock deformation and roof support has been achieved. The study can be applied for the entire Tashan coal mine, and has significant implication for engineering projects with similar geological and mining conditions.